Synthesis and Characterization of Vanillin Semicarbazones - Venkateshhan, N.; Ravichandran, V.; Selvakumar, D.; Lavakumar, V. (Asian Journal of Chemistry, 2011)
Semicarbazones have a great interest because of their chemistry and biological activities for the treatment of various human ailments. A series of seven vanillin semicarbazones (3a-g) were synthesized by reflux of aryl semicarbazides with appropriate carbonyl compound in the presence of glacial acetic acid. The aryl semicarbazides (2a-g) were synthesized from aryl carbamates by reacting with hydrazine hydrate and ethanol on hydrazinolysis. The aryl carbamates (1a-g) were obtained by the reaction between phenyl chloro formate and aniline/substituted aniline in anhydrous ether in the presence of sodium hydroxide. The structure of the newly synthesized compounds was established by various analytical techniques such as IR, 1H NMR and MASS spectral studies.